“I don’t want to have anything to do with someone suspected of COVID-19”: a genuine infection avoidance interests or inappropriate concerns related to stigma? - Sulemana Abubakari; Edward Apraku; Solomon Nyame; Francis Agbokey; Samuel Afari-Asiedu; Stephaney Gyaase; Thomas Gyan; Lawrence Gyabaa Febir; Livesy Abokyi; Kwaku Poku Asante (Journal of Public Health in Africa, 2023)
Background: Human existence is being challenged by an outbreak of coronavirus disease 2019 (COVID-19) caused by the virus SARS-CoV-2 that began in Wuhan, China in December 2019. Efforts to avoid the spread of COVID-19 are undermined by the appearance of disease-associated avoidance of infected persons due to reasons such as social stigma and discrimination.